Mature compost enhanced the harmlessness level in co-composting swine manure and carcasses in large-scale silo reactors - Jiao, Ziwei; Zhang, Liping; Zhang, Ake; Li, Ruoqi; Zhang, Kui; Wu, Zhen; Kang, Zitong; Wei, Yuquan; Zhang, Longli; Wang, Yue; Shi, Xiong; Li, Ji (Frontiers in Microbiology, 2024)
This study aimed to investigate the impact of incorporating mature compost on the harmlessness and maturity level of composting from swine manure and carcasses from industrialized pig farms in continuously running large-scale silo reactor systems. The potential human or animal bacterial pathogens and core bacterial community in composting were analyzed by high-throughput sequencing of 16S rRNA gene amplicons. The results showed that the addition of mature compost in the GD group significantly increased the temperature of all depths, the accumulated temperature of compost, and the germination index (75.43%) compared to that in the HN group without mature compost. High-throughput sequencing revealed that the dominated genera in GD were Ureibacillus, Lactobacillus, Corynebacterium, Staphylococcus, and Jeotgalicoccus, and the addition of mature compost could significantly increase the relative abundance of Ureibacillus (16.82%) that was associated with the biodegradation of organics. A total of 421 potential bacterial pathogens were detected, and the dominated genera of pathogens were Streptococcus, Staphylococcus, and Anaerococcus. The potential pathogen in the GD group with mature compost was reduced from 7.16 to 0.77%, which was significantly lower than that (2.97%) in the HN group. Together, these findings revealed that mature compost addition in large-scale reactor composting could accelerate the harmless and humification process, providing an effective and environmentally friendly scheme to deal with the main organic wastes in intensive pig farms.